The Preoperative Level of B-Type Natriuretic Peptides and the Results of Clinical and Functional Studies of Cardiosurgical Patients - I. A. Kozlov; I. Ye. Kharlamova; L. A. Krichevsky (Общая реаниматология)
Objective: to study the plasma content of B-type natriuretic peptides in coronary heart disease patients prepared for surgery under extracorporeal circulation and to assess the association of the level of these biomarkers with the data of clinical and functional studies. Material and methods. The levels of active B-type natriuretic peptide were determined by immunofluoresence assay in the blood of 52 patients aged 57.8±1 years. The patients’ baseline clinical condition was in New York Heart Association (NYHA) Functional Class I—IV. The left ventricular ejection fraction was 59.6±1.2%. The plasma concentration of the inactive N-terminal fragment of the BNP prohormone (NT-proBNP) was estimated by electric chemiluminescence technique in 61 patients aged 54.6±1.18 years. The patients’ clinical condition was in NYHA Functional Class II—IV. The left ventricular ejection fraction was 51.5±1.6%. Results. The plasma content of B-type natriuretic peptide in the examinees was 48.5±5.9 pg/ml. The level of the biomarker correlated with the NYHA functional class (r=0.4; p=0.005), the electrocardiographic signs of postinfarct cardiosclerosis (r=0.29; p=0.04), and left ventricular ejection fraction (r=-0.41; p=0.003), and end-systolic volume (r=0.32; p=0.03). The plasma concentration of inactive NT-proBNP was 659.4±91.6 pg/ml. The level of the biomarker correlated with the NYHA functional class (r=0.4; p=0.002), the stage of circulatory insufficiency as described by I. D. Strazhesko and V. Kh. Vasilenko (r=0.49; p=0.001), and left ventricular ejection fraction (r=-0.45; p=0.001), and end-diastolic (r=0.39; p=0.002) and end-systolic (r=0.42; p=0.001) volumes. In patients with the values of the biomarker of less than 1000 pg/ml, the latter was related to age (r=0.3; p=0.047). Conclusion. The study of the level of B-type natriuretic peptides in cardiosurgical patients with coronary heart disease, prepared for surgery under extracorporeal circulation, suggests that the content of both peptides is obviously correlated with the conventional clinicofunctional parameters. At the same time, the moderate or weak pattern of all correlations indicated the independent diagnostic value of biomarkers. Key words: B-type natriuretic peptides, brain nautri-uretic peptide (BNP), N-terminal fragment of the BNP prohormone (NT-proBNP), coronary heart disease, surgery under extracorporeal circulation.